Education level and chronic liver disease by aetiology: A proportional mortality study. Issue 12 (December 2015) - Fedeli, Ugo; Avossa, Francesco; Goldoni, Carlo Alberto; Caranci, Nicola; Zambon, Francesco; Saugo, Mario
Abstract: Background: Data are lacking on mortality from chronic liver diseases of different aetiology by education level. Aims: To investigate the association between education level and mortality from alcoholic, viral, and non-viral/non-alcoholic chronic liver disease. Methods: Proportional mortality was investigated in 2011–2013 in the Veneto Region (Italy). Odds ratios were estimated by conditional logistic regression with deaths from liver cirrhosis, liver cancer, and viral hepatitis as cases, and all other deaths as controls. Disease aetiology was determined from all conditions mentioned in the death certificate. Results: Overall chronic liver disease proportional mortality was higher in males (OR 1.37, 95% CI 1.18–1.60) and females (OR 1.72, 95% CI 1.29–2.30) with primary education than in subjects with higher educational level. The risk for alcohol-related and non-viral/non-alcohol-related disease significantly increased with lower education in both genders. Conclusions: Proportional mortality analysis of multiple causes of death records showed an association between education and chronic liver diseases with alcoholic and non-viral/non-alcoholic aetiology.